The Localization of a Spherical Ferromagnetic Microparticle in an Oscillating Magnetic Field in a Liquid Stream - Gorobets, O.Yu.; Potyemkin, M.M. (Ukrainian Journal of Physics, 2012)
The model of magnetic tweezers in a rapidly oscillating alternating magnetic field, which allows one to estimate the movement of a ferromagnetic magnetically soft microparticle in a magnetic trap and to localize it in a liquid, is offered. The estimations of the strength and the frequency of an oscillating alternating magnetic field and the size of a spherical microparticle are carried out. The movement trajectory of a spherical microparticle is calculated as well.